Justice and Legal Certainty in the Annulment of Divorce Decisions: The Perspective of Principles Complicating Divorce - Latifah, Tasya Putri (Jurnal El-Thawalib, 2025)
The annulment of a divorce decision highlights a divergence in judicial perspectives regarding the granting of divorce. One of the primary considerations is that the divorce petition was deemed premature, as it did not yet fulfill the requirements for a divorce to be granted. In annulling the divorce, the judges sought to consider all relevant aspects, including legal justice and the principle of legal certainty. This consideration forms the basis of the present study, which aims to analyze how the judges’ legal reasoning reflects these principles in rendering a decision that annulled the divorce. This study employs a qualitative, normative juridical approach. The primary data sources are the case files Number 1/Pdt.G/2025/PTA.Yk and Number 422/Pdt.G/2024/PA.Wt, while supplementary sources included books, journal articles, and statutory regulations such as the Marriage Law, the Compilation of Islamic Law (KHI), and SEMA Number 3 of 2023. Data collection was conducted through documentation, and analysis was performed using a descriptive approach based on inductive reasoning. The research revealed that the appellate panel of judges annulled the previous divorce decision based on consideration of justice and legal certainty. From the perspective of legal justice, the judges determined that the divorce petition was premature, as it did not meet the 6 months separation requirement, and there was no evidence of domestic violence during the marriage; therefore, the divorce could not be granted. From the perspective of legal certainty, the panel referred to the principle of complicating divorce proceedings, as stipulated in SEMA Number 3 of 2023. Consequently, the divorce was annulled for failing to meet the substantive requirements of the law. Based on these considerations of justice and legal certainty, the panel of judges annulled the divorce, thereby restoring legal certainty regarding the marital status of the husband and wife.